(untitled) (Annals of Medical Research, 2023)
Aim: A critical health problem that affects people all around the world is vitamin D deficiency. Fundamentally, obesity and vitamin D deficiency are acknowledged as major global public health problem. In this study, we examined the connection between low vitamin D levels and Body Mass Index (BMI), as well as the association between demographic factors and vitamin D. Materials and Methods: 207 participants who were 18 years old or older and had ever been diagnosed with a chronic disease were included in the study. The participants filled out a questionnaire to analyze their demographic characteristics and physical activity levels. As well as evaluating the body mass index, serum vitamin D levels were tested. Results: It was reported that among the study participants, there was a substantial positive association between levels of physical activity and vitamin D levels. Vitamin D levels were found to be significantly negatively correlated with participant weight and BMI. Increasing weight and BMI lead to a reduction in vitamin D levels. It was demonstrated that gender, body mass index, physical activity level, marital status, vitamin D-containing food consumption state and consumption amount, vitamin D supplementation state, ways of going to work, daily exposure to sunlight, seasonal exposure to sunlight affects vitamin D levels. Conclusion: The study group was found to have very high levels of vitamin D insufficiency and deficiency, and there was a strong association between 25-hydroxy vitamin D3 (25(OH)D3) serum level and physical activity level and BMI.